PISA-LIKE: FOOTBALL CONTEXT IN ASIAN GAMES - Ranni Permatasari; Ratu Ilma Indra Putri; Zulkardi Zulkardi (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2018)
This study aimed to develop a set of PISA-like mathematics problems on uncertainty and data content using football as a context which was valid, practical and had potential effects on students’ mathematical literacy ability. The method used in this study is design research with development studies type which had two stage: the preliminary and formative evaluation. Tenth-grade students of senior high schools in Palembang were involved in this research. This study produced a set of PISA-like mathematics problems at 3, 4, and 5 level. In this case, student’s strategies used some ability in solving one of the problems, namely mathematizing, representation, and communication ability. There were 16 out of 35 students using mathematizing and communication ability, 10 out of 35 students using representation and communication ability, and 9 out of 35 students only using communication ability. Also, the results of the interview with some students showed that they liked to do such PISA-like mathematics problems because they could improve their literacy ability in solving the PISA-like problem.